PDTM-09. KCNA1 IS A MOLECULAR TARGET OF A NOVEL SET OF microRNAs THAT DRIVE PEDIATRIC GBM INVASION. (6th November 2017) - Qi, Lin; Huang, Yulun; Mao, Hua; Kogiso, Mari; Zhao, Xiumei; Du, Yuchen; Lindsay, Holly; Baxter, Patricia; Su, Jack; Man, Chris; Perlaky, Laszlo; Li, Xiao-Nan
Abstract: Glioblastoma (GBM) is the most malignant brain tumor that occurs in both adults and children. Diffuse invasion into normal brain tissue is one of the major features that makes GBM particularly difficult to treat. While direct comparison of matched invasive (GBMINV) and tumor core (GBMTC) cells would facilitate the discovery of molecular drivers of GBM invasion, GBMINV cells are extremely difficult to obtain from patients. To overcome this barrier, 6 patient derived orthotopic xenograft (PDOX) mouse models of pediatric GBM were utilized to isolate GBMTC and GBMINV cells. Global profiling of 768 human microRNA using a real-time PCR-based Taqman system identified 23 microRNAs were upregulated in the GBMINV cells as compared with the matching GBMTC cells. Functional validation was performed by lentivirus-mediated silencing of miR-126, miR-487b and miR-369-5p, the top three overexpressed microRNA in the GBMINV cells. Compared with the control cells, silencing of miR-126, miR-487b or miR-369-5p in GBMINV cells resulted in significant inhibition of cell migration in vitro (without affecting tumor proliferation) (P<0.05), and the blocking of in vivo invasion. The depth of invasive fronts was remarkably decreased (P<0.05) in mouse brains. Whole genome gene expression profiling from the same pairs of GBMINV and GBMTC cells identified a subset of genes regulated by miR-126 (n=74), miR-487b (n=46) and miR-369-5p (n=2) that occurred in at least 4 of the 6 pairs. Surprisingly, KCNA1 was the only gene that was co-regulated by all three miRNAs and significantly over-expressed in the GBMINV cells (p=0.033). Targeting KCNA1 by specific inhibitor ADW1 and Agi suppressed GBMINV cell invasion in vitro without affecting tumor proliferation. In conclusion, our strategy of utilizing functionally validated matching pairs of GBMINV and GBMTC cells has identified KCNA1 as the molecular target of a novel set of microRNAs (miR-126, miR-487b and miR369-5p) that drive GBM invasion.